An ephemeral anomaly. The metamorphoses of the Eskimo Language School: 1968-1999 - Mallon, Mick (Études/Inuit/Studies, 2005)
AbstractThis is an informal history of the now defunct Eskimo Language School and its successors from 1968 to its demise in 1999. The Eskimo Language School was an institution set up by the Department of Indian Affairs and Northern Development of the federal government of Canada in order to provide Inuktitut as second language training to federal and North West Territorial employees. Private students were also admitted if there was space. It could therefore be considered an early effort to ameliorate the effects of the language shift from Inuktitut to English that was the inevitable result of the incursion of a massive southern bureaucracy into the Arctic. In addition, the school had a secondary effect on the situation as it provided a casual form of apprenticeship in applied linguistics to the young Inuit who spent time there as instructors. Its story is also that of an anomaly, a creation of the bureaucracy that escaped the usual stultifying institutional control for most of its existence. At the end of the paper there is a brief discussion of the problems involved in teaching a polysynthetic language to speakers of languages such as English and French, with suggestions for solutions.